RASA SYUKUR, DUKUNGAN SOSIAL, DAN KESEJAHTERAAN PSIKOLOGIS PURNA JABATAN PEGAWAI NEGERI SIPIL - Kenya Arum Kistianingsih; Eny Purwandari (Program Studi S1 Psikologi, 2020)
Retirement is a very complex lifestyle transition. If you aren’t ready to deal with these changes then feel unhappiness will most likely occur. Meeting the needs of psychological well-being is a form happiness. Gratitude is a form of happiness expressed by someone and is accosiated to psychological well-being. In addition to gratitude, social support can have a positive impact on individual’s helath and well-being. This studi aims to determine the relationship of gratitude and social support for psychological well-being in post-service civil servants. The subjects used in this study were full-time civil servants, totaling 80 men and women. In this study, Sampling using incidental sampling techniques. This study uses a quantitative approach. The data collection tools used in this study were gratitude scale, social support scale, and psychological well-being scale. Data analysis was performed with multiple regression tests. Based on the result of the analysis shows that there is a positive and significant relationship between gratitude and social support with psychological well-being in the post of civil service.